# Simplify (x-2)^2

*print*Print*list*Cite

### 4 Answers

You need to expand the binomial using the formula `(a-b)^2 = a^2 - 2ab + b^2` .

Hence, substituting x for a and 2 for b yields:

`(x - 2)^2 = x^2 - 4x + 4`

You may also use distributive multiplication such that:

`(x - 2)^2 = (x - 2)(x - 2) = (x-2)*x +(x-2)*(-2)`

Opening the brackets yields:

`(x - 2)^2 = x*x - 2*x + x*(-2) - 2*(-2)`

`(x - 2)^2 = x^2 - 2x - 2x + 4`

`(x - 2)^2 = x^2 - 4x + 4`

**Hence, expanding the binomial `(x-2)^2` yields `(x - 2)^2 = x^2 - 4x + 4.` **

### User Comments

I solved that kind of problem when i was in school.(x-2)^2 is a simple quadratic equation and it can be solve by using (a-b)^2 formula.green cookware

It's simple quadratic equationYou can used the formula of (a-b) the whole square.you have to just factorized the equation.luxury vacation bali

(x-2)^2=(x-2)(x-2)

Answer=x^2-4x-4